2018
DOI: 10.1016/j.neuro.2017.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Association between prenatal exposure to organochlorine pesticides and the mental and psychomotor development of infants at ages 6 and 18 months: The Hokkaido Study on Environment and Children’s Health

Abstract: Organochlorine pesticides (OCPs) are environmental contaminants that persist in the environment and bioaccumulate through the food chain in humans and animals. Although previous studies have shown an association between prenatal OCP exposure and subsequent neurodevelopment, the levels of OCPs included in these studies were inconsistent. A hospital-based prospective birth cohort study was conducted to examine the associations between prenatal exposure to relatively low levels of OCPs and neurodevelopment in inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 26 publications
2
10
0
Order By: Relevance
“…Several studies have shown that prenatal exposure to OPs are related to cognitive deficits (Bouchard et al, 2011; Engel et al, 2016; Eskenazi et al, 2007; Philippat et al, 2018; Rauh et al, 2012) and ASD‐related traits (Eskenazi et al, 2007; Furlong et al, 2014; Sagiv et al, 2018). However, there are inconsistencies regarding associations between OC exposure and child neurodevelopmental outcomes (Eskenazi et al, 2006; Gaspar et al, 2015; Lyall, Croen, Sjödin, et al, 2017; Yamazaki et al, 2018), and some studies have reported sex differences (Braun et al, 2014; Gaspar et al, 2015; Pan et al, 2009; Sioen et al, 2013), which we did not have sufficient power to address here. Several mechanisms may underlie these potential associations.…”
Section: Discussionmentioning
confidence: 84%
“…Several studies have shown that prenatal exposure to OPs are related to cognitive deficits (Bouchard et al, 2011; Engel et al, 2016; Eskenazi et al, 2007; Philippat et al, 2018; Rauh et al, 2012) and ASD‐related traits (Eskenazi et al, 2007; Furlong et al, 2014; Sagiv et al, 2018). However, there are inconsistencies regarding associations between OC exposure and child neurodevelopmental outcomes (Eskenazi et al, 2006; Gaspar et al, 2015; Lyall, Croen, Sjödin, et al, 2017; Yamazaki et al, 2018), and some studies have reported sex differences (Braun et al, 2014; Gaspar et al, 2015; Pan et al, 2009; Sioen et al, 2013), which we did not have sufficient power to address here. Several mechanisms may underlie these potential associations.…”
Section: Discussionmentioning
confidence: 84%
“…In the Sapporo birth cohort, for neurodevelopment, prenatal exposure to cis-heptachlor epoxide, an organochlorine pesticide, had a negative association with mental development at 18 months, but not at 6 months of age [ 53 ]. Prenatal exposure to total non-ortho PCBs was negatively associated with the cognitive ability in males while several dioxin-like compounds were positively associated with the achievement score (i.e., the basis of intelligence in all children at 42 months) [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…They indicated that hexachlorobenzene (HCB) was negatively associated with TSH in cord serum. For heptachlor epoxide, Yamazaki et al [57] also found a significant inverse association between prenatal low-level exposure to cis -heptachlor epoxide and the MDI at the age of 18 months, as evaluated using the BSID-II in Japan [57]. In the case of the growth hormone IGF-1, few reports have examined the correlations between OCPs in cord blood or breast milk and cord blood IGF-1 in neonates, particularly for newborns.…”
Section: Discussionmentioning
confidence: 99%